Systematic Literature Review (SLR) MSMEs Performance: Themes, Theories and Integrative Frameworks - Br Purba, Neni Marlina; Kesuma, Sambas Ade; Muda, Iskandar (Universitas Jember, 2025)
This study is a Systematic Literature Review (SLR) conducted to systematically view, review, map and focus on various previous studies that are dominant on themes, theories and frameworks in the performance of Micro, Small and Medium Enterprises (MSMEs). This SLR was conducted by mapping in detail from 51 articles indexed by Scopus and indexed Q1, Q2, Q3, and Q4 published during the last 10 years, namely the period 2016 - 2025. The analysis in this SLR is based on the category of themes (variables), theories, methodologies, and research objects as well as matters related to the research findings. Based on the results of the analysis of several dominant variables in the study such as digital marketing, e-commerce, business strategy, financial literacy, technology adoption. The dominant method used in MSME performance research is the quantitative research method with SEM statistical techniques and SmartPLS and AMOS analysis methods. While Resource-Based View (RBV) is the most important theory used, followed by the Innovation Theory and Technology Adoption Model (TAM) theories. Keywords: MSMEs, Business Performance, Systematic Literature, Digitalization, Strategic Orientation